STUDY OF THE SENSITIZING EFFECT AND EFFECT ON CARDIAC FUNCTION OF THE DRUGS ESSIN/HP-BETTA-CD AND TAUCIN UNDER EXPERIMENTAL CONDITIONS - Sh.T. Makhmaraimov; Z.Kh. Amonova; M.Zh. Allaeva; D.D. Achilov (Central Asian Journal of Medicine, 2025)
The aim of the study was to investigate the degree of sensitizing action and the effect on cardiac function of the preparations Essin/HP-betta-CD and Taucin on laboratory animals: rabbits and guinea pigs. Determination of the sensitizing effect of the preparation Essin/HP-betta-CD: on the 10th, 15th and 20th days of the experiment after instillation of an aqueous solution of the preparation into the conjunctiva of the eye, the guinea pigs blinked their right eye for a short time. They did not open the right eye. Within 72 hours after exposure to the preparation, itching of the skin of the eyelids, edema of the mucous membrane, infiltrates in the limb were not detected. The effect of Essin/HP-betta-CD on the number of heartbeats, the height of the R wave and the duration of the Q-T, QRS and S-T intervals was studied using electrocardiograms of rabbits under light anesthesia. Electrocardiograms of rabbits were recorded 10 and 30 minutes after administration of Essin/HP-betta-CD. The effect of Taucin on cardiac function was studied using electrocardiograms (ECG) in experimental rabbits under light anesthesia. Heart rate (HR), R wave height, QT, QRS, and S-T intervals were analyzed. Taucin was administered to rabbits orally at doses of 30 and 70 mg/kg once, with ECG readings monitored at intervals of 10 and 30 minutes.